Voltage Drop and Power Loss Mitigation on SGN-14 via SGN-15 Feeder Design in Distribution System ULP Magelang - Haqrodji Prabu Yasya; Deria Pravitasari; Agung Trihasto; Andriyatna Agung Kurniawan (Aviation Electronics, Information Technology, Telecommunications, Electricals, and Controls (AVITEC), 2026)
Feeder SGN-14 of PT PLN (Persero) ULP Magelang operates under overload conditions, significantly degrading voltage quality and increasing technical losses. PLN (Perusahaan Listrik Negara) is Indonesia’s State Electricity Company, while ULP (Unit Layanan Pelanggan) refers to a customer service unit. This study designs Feeder SGN-15 as a 20 kV load-splitting feeder supplied from Sanggrahan Substation and terminating near KH. Maksum Street (Tempuran). The feeder is 20.7 km long and routed close to the load centre to reduce line losses. Network performance is assessed using ETAP load-flow simulations and independent GNU Octave calculations of voltage profile, current, and power/energy losses, referenced to SPLN T6.001:2013 with a 10% voltage-drop limit. The proposed feeder uses 8,152 m of insulated MVTIC and 12,584 m of AAAC conductors, supported by 238 concrete poles, together with required switching devices, line accessories, and four CSP transformers. After reconfiguration, the maximum voltage drops on SGN-14 decreases from 12.82% to 6.5%, while SGN-15 operates at about 4.95%, ensuring all buses comply with SPLN T6.001:2013. Technical losses on SGN-14 fall from 388.711 to 112.337 (W/kWh), and SGN-15 contributes 81.130 (W/kWh), giving total post-reconfiguration losses of 195.467 (W/kWh). The reduction in energy-loss cost yields an estimated saving of Rp228.82 million per month, lowering losses from Rp460.32 million/month to Rp231.44 million/month. Unlike studies that optimize only switch states or voltage-regulator placement, this work shows that adding a new 20 kV feeder can jointly improve voltages, reduce losses, and deliver tangible benefits for the distribution utility.